Managing Multiple Disadvantages: The Regulation of Complex Needs in Emergency Shelters for the Homeless. Issue 3 (2nd July 2016) - Quirouette, Marianne
ABSTRACT: People who face multiple disadvantages (re: poverty, criminalization, discrimination, addiction, health/mental health, disabilities) make up the majority of the homeless shelter population on a daily basis. This group challenges practitioners and existing service structures, and the author shows how these challenges shape (1) collaboration with "complex-need" clients, (2) triage and case prioritization, and (3) assessments of housing readiness. Pulling from policy and organizational document analysis as well as 20 in-depth interviews with emergency shelter practitioners, the author argues that institutional recognition of people's "complicated" needs translates into tighter regulation and/or decreased support.